An analytical review of Halffter’s Mexican transition zone, and its relevance for evolutionary biogeography, ecology and biogeographical regionalization - Halffter, Gonzalo; Morrone, Juan J. (Zootaxa, 2017)
The Mexican transition zone (MTZ) is the complex area where the Neotropical and Nearctic biotas overlap, including south-western United States, Mexico and a large part of Central America extending to the Nicaraguan lowlands. In a strict sense, it corresponds to the mountain highlands of Mexico, Guatemala, Honduras, El Salvador and Nicaragua. We review Halffter’s theory explaining the biotic evolution of the MTZ, including the description and discussion of the distributional patterns and cenocrons recognized within it. Distributional patterns are generalizations that help analyse and compare distributions of different taxa. Cenocrons correspond to sets of taxa that share the same biogeographic history, constituting identifiable subsets within the transitional biota by their common biotic origin and evolutionary history. The heuristic value of distributional patterns and cenocrons lies in their application to formulate hypotheses on biotic assembly in the geographical-ecological space, to analyse the ecological response to anthropic impact, to analyse altitudinal patterns and to undertake time-slicing in cladistic biogeography. Three case studies are analysed with some detail: the Neotropical genus Canthon and the tribe Phanaeini and the Holarctic/Nearctic subfamily Geotrupinae. The Paleoamerican and Mexican Plateau cenocrons define the approximate boundaries of the MTZ, whereas the Mountain Mesoamerican, Nearctic and Typical Neotropical cenocrons correspond to the more conventional boundaries of the Nearctic and Neotropical regions. The biotic assembly of the MTZ is summarized into five stages: in the Jurassic-Cretaceous, the Paleoamerican cenocron (later diversified into five varieties) extended in Mexico; in the Late Cretaceous-Palaeocene, the Mexican Plateau cenocron dispersed from South America; in the Oligocene-Miocene, the Mountain Mesoamerican cenocron dispersed from the Central American Nucleus; in the Miocene-Pliocene, the Nearctic cenocron dispersed from northern North America; and in the Pleistocene, the Typical Neotropical cenocron dispersed from South America. Finally, we review the impact of Halffter’s MTZ, with particular reference to dispersal, track, cladistic biogeographic, endemicity and phylogeographic analyses, as well as biogeographic regionalization.